Job, Milley, Foote, Williamson, Monroe. (1930)
1 photograph : sepia toned 13.5 x 8 cm Samuel F. Milley, Samuel J. Foote, Robert Brown Job, T. Williamson and Walter Stanley Monroe sitting on the front porch of the Fomowa Clubhouse. Title from album caption. Samuel F. Milley (1867-1939) was born in St. John's in 1867. Milley was a prominent dry goods merchant in St. John's from 1890's and was a member of the Legisaltive Council for more than 30 years. Milley died in Montreal on February 12, 1939.Walter Stanley Monroe (1871-1952) was born in Dublin, Ireland, son of John and Elizabeth (Moule) Monroe. Married Helen Smith. In 1923 Monroe entered politics and ran unsuccessfully against William Coaker in Bonavista. William Warren appointed Monroe Minister in his second administration formed in 1924. Monroe was appointed to the Legisaltive Council in 1933. Robert Brown Job (1873-1961), son of Agnes (Brown) and Thomas Raffles Job, was born in Waterloo, England. Married (1) Alice Warren; (2) Emilie (Mare) Warren. In 1899 he became partners in Job Brothers & Co. In 1928 Job was appointed to the Legisaltive Council and served in that body until the introduction of Government by Commission in 1934. He was a local historian and contributed several articles to the Newfoundland Quarterly. Job died on September 6, 1961. Samuel J. Foote (1873-1936) was born in Grand Bank in 1873. Foote was called to the Newfoundland Bar in 1899 and went to practice with Sir James Winter. Foote entered into politics in 1904. Foote died on December 8, 1936. Good An album containing 323 black and white photographs and 25 pages of text, covering the years 1914 to 1937 of the FOMOWA Fishing Club on the Grand Codroy River on the west coast of Newfoundland. The album's images have been digitized as separate items.